Literature Study: The Role of the Indonesian Child Protection Commission in the Protection of Abandoned Children - Elan Elan; Edi Hendri Mulyana; Alma Permata Fitriani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The Indonesian Child Protection Commission is an independent state agency assigned based on Law No. 23 of 2002 concerning Child Protection. A neglected child is a child whose parents for some reason neglect and/or are unable to carry out their obligations so that the child's physical, spiritual and social needs are not met. Cases of abandoned children are widespread cases in Indonesia that need to be considered by the government in protecting and fulfilling children's rights. In general, neglected children experience multiple problems such as economic difficulties, lack of attention and affection from their parents, and cannot get maximum educational services. This research uses the literature study method, the literature study method is all data collected from journals, books or other sources. In this study, researchers looked for studies that were relevant to the research being conducted, reviewing existing research.